2009
DOI: 10.3133/sir20095160
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Interactions between Surface Water and Near-Stream Groundwater along Fish Creek, Teton County, Wyoming, by Using Heat as a Tracer

Abstract: Fish Creek, a tributary of the Snake River, is about 25 river kilometers long and is located in Teton County in western Wyoming near the town of Wilson. Local residents began observing an increase in the growth of algae and aquatic plants in the stream during the last decade. Due to the known importance of groundwater to surface water in the area, the U.S. Geological Survey (USGS), in cooperation with the Teton Conservation District, conducted a study to characterize the interactions between surface water and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…VS2DH is a modification of VS2DT (Healy, 1990), which was developed for simulating solute transport in variably saturated porous media such as ephemeral streambeds or through the unsaturated zone (Constantz et al, 2001; Blasch et al, 2006). Recent studies also have shown the effectiveness of using heat to model energy transport to derive hydraulic properties of alluvial aquifers and wetlands (Su et al, 2004; Burow et al, 2005; Eddy‐Miller et al, 2009). A previous study at the Bogue Phalia study site developed one‐dimensional models using VS2DH, which verified GWSW exchange, but did not include transport processes (Barlow and Coupe, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…VS2DH is a modification of VS2DT (Healy, 1990), which was developed for simulating solute transport in variably saturated porous media such as ephemeral streambeds or through the unsaturated zone (Constantz et al, 2001; Blasch et al, 2006). Recent studies also have shown the effectiveness of using heat to model energy transport to derive hydraulic properties of alluvial aquifers and wetlands (Su et al, 2004; Burow et al, 2005; Eddy‐Miller et al, 2009). A previous study at the Bogue Phalia study site developed one‐dimensional models using VS2DH, which verified GWSW exchange, but did not include transport processes (Barlow and Coupe, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Reconnaissance based on contrast in temperature at the sediment‐water interface is now a commonly used method to locate areas of focused and rapid groundwater discharge to surface water [e.g., Blume et al ., ; Eddy‐Miller et al ., ; Henderson et al ., ; Krause et al ., ; Mwakanyamale et al ., ; Sebok et al ., ]. During summer, shallow surface water is warm and discharge of groundwater, which usually is close to the annual‐average air temperature, is colder and provides a measurable temperature contrast; the opposite pattern is expected during winter [e.g., Slater et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Focused groundwater discharge may be caused by the interaction between upwelling water and discontinuous buried lenses of peat and clay [Krause et al, 2012], or even through extreme macropore structures such as ''peat pipes'' [Briggs et al, 2016]. Identifying these areas of focused discharge is critical, whether quantifying total groundwater discharge to a lake, embayment, or a stream reach [e.g., Briggs et al, 2012; Reconnaissance based on contrast in temperature at the sediment-water interface is now a commonly used method to locate areas of focused and rapid groundwater discharge to surface water [e.g., Blume et al, 2013;Eddy-Miller et al, 2009;Henderson et al, 2009;Krause et al, 2012;Mwakanyamale et al, 2012;Sebok et al, 2013]. During summer, shallow surface water is warm and discharge of groundwater, which usually is close to the annual-average air temperature, is colder and provides a measurable temperature contrast; the opposite pattern is expected during winter [e.g., Slater et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…The water and heat flow modeling approach for analysis of continuous T and H measurements has the advantage of being able to incorporate streambed heterogeneity and multidimensional flow, as well as rapid, transient responses to changes in stream stage and GW head. Heat has been used as a tracer to characterize temporal dynamics of 1‐D vertical streambed flux [ Bhaskar et al ., ; Briggs et al ., ; Essaid et al ., ; Gariglio et al ., ; Hatch et al ., ; Jensen and Engesgaard , ; Keery et al ., ; Lautz , ; Tristram et al ., ], 2‐D vertical and lateral streambed flux perpendicular to the stream channel [ Barlow and Coupe , ; Bartsch et al ., ; Constantz et al ., ; Eddy‐Miller et al ., ; Essaid et al ., ; Nützmann et al ., ], and 3‐D streambed flux for a 4 m thick aquifer slice perpendicular to the axis of the stream [ Karan et al ., ].…”
Section: Introductionmentioning
confidence: 99%